Fostering a Class Positive Environment in Elementary Schools Using Positive Discipline Approach - Utami, Putri; Maryanto; Atim Rinawati; Muhyidin; Umi Arifah; Imam Subarkah; Siti Fatimah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
A conducive learning environment impacts children's development. Schools, as educational institutions, play a crucial role in creating a supportive and child-friendly learning environment. The objective of this study is to analyze the implementation of a positive discipline approach in efforts to establish a conducive learning environment for elementary school students. This research employs a qualitative phenomenological approach. The study was conducted at Jemur Public Elementary School in Kebumen. The subjects of this study include the school principal, teachers, and students. Data collection techniques involve interviews, observations, and documentation studies. Triangulation techniques were used to ensure data validity. Data analysis was carried out using the Miles & Huberman & Saldana model. The results of the study indicate that the positive discipline approach has been implemented effectively at Jemur Public Elementary School in Kebumen. However, collaboration between parents and the school needs to be further enhanced to ensure children can learn comfortably wherever they are. Strong collaboration among schools, families, and the community is recommended based on this research.